OECD employment outlook 2003 : towards more and better jobs - (:unkn) unknown (My University, 2003)
"How best to promote job opportunities, particularly for people on the fringes of labour markets? This is one of the issues addressed in the 2003 edition of the OECD's annual Employment Outlook. It argues that unemployment in OECD countries has so far risen more slowly during the current economic slump than in past downturns, thanks to structural changes. But it also says that countries must do more to remove barriers to job creation, notably for groups under-represented in the labour market, and proposes concrete strategies for doing so. Chapter 1: More and Better Jobs? - Aggregate Performance during the Past Decade Chapter 2: The Labour Mobilisation Challenge - Remaining Pockets of Excess Inactivity and Barriers to Moving up Job Ladders Chapter 3: Making Work Pay - Making Work Possible Chapter 4: Benefits and Employment, Friend or Foe? Interactions Between Passive and Active Social Programmes Chapter 5: Upgrading Workers' Skills and Competencies" (author's abstract, IAB-Doku) ((en))
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.3.3.3 Mobilität; G 1.2.2.1 Lohn- & Tarifsysteme; G 1.2 Arbeitsmarkt; S 4.3 Steuerung; G 1.2.2.2 Soziale Sicherungssysteme; Arbeitsmarktentwicklung; Beschäftigungsentwicklung; Arbeitskräftemobilität; Niedriglohn; Arbeitsmarktpolitik; Aktivierende Arbeitsmarktpolitik; Weiterbildungsförderung; Arbeitslosenunterstützung; Sozialhilfe; Quantitative Angaben; OECD; 1991-2003